2022
DOI: 10.2106/jbjs.21.01157
|View full text |Cite
|
Sign up to set email alerts
|

In Situ-Forming Fibrin Gel Encapsulation of MSC-Exosomes for Partial-Thickness Rotator Cuff Tears in a Rabbit Model

Abstract: Background:Current nonoperative treatments for partial-thickness rotator cuff tears (PTRCTs) have limited effectiveness in preventing tear progression or promoting tendon healing. This study aimed to establish a rabbit model using in situ-forming fibrin gel containing adipose stem cell-derived exosomes (ASC-Exos/fibrin) to treat PTRCTs.Methods:Fifty-six rabbits (112 shoulders) were included in this study and assigned to 4 groups: the control group (32 shoulders; PTRCTs without treatment), the fibrin group (32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…The results of this study provide supportive data for ADMSC young -EVs in tendinopathy therapy and highlight their effects on both tenocytes and macrophages. Two previous studies on ADMSC-derived EVs in tendon repair did not provide the age of donors [ 31 , 32 ]; however, it was natural to conjecture that no ADMSCs from aged mice or humans were used in their studies. Thus, our data were consistent with previous studies, and additional knowledge was provided for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study provide supportive data for ADMSC young -EVs in tendinopathy therapy and highlight their effects on both tenocytes and macrophages. Two previous studies on ADMSC-derived EVs in tendon repair did not provide the age of donors [ 31 , 32 ]; however, it was natural to conjecture that no ADMSCs from aged mice or humans were used in their studies. Thus, our data were consistent with previous studies, and additional knowledge was provided for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has indicated the potential of mesenchymal stem cells (MSCs) in mitigating degenerative changes associated with RCT, thereby improving surgical repair outcomes. [76][77][78] This potential can be attributed to their ability for multilineage differentiation. Nonetheless, it is noteworthy that the regenerative capacity of MSCs may be compromised with aging, limiting their effectiveness in addressing aging-related muscle degeneration.…”
Section: Aging Impairs Muscle Regenerationmentioning
confidence: 99%
“…Fu et al injected an ADSC-Exos-hydrogel complex into the shoulders of rats in a rotator cuff injury model and observed enhanced rotator cuff repair and tendon-bone healing attributed to ADSC-Exos promoting the differentiation of tendon-derived stem cells [ 156 ]. Wang et al [ 157 ] demonstrated that the local administration of a fibrin gel containing ADSC-Exos could significantly prevent tear progression, enhance the biomechanical properties of the injured tendon, and promote high-quality tendon healing in a rabbit model of partial-thickness rotator cuff tears.…”
Section: Adscs and Adsc-based Therapies For Musculoskeletal Regenerationmentioning
confidence: 99%